DEVELOPMENT OF BEEF CATTLE AGRIBUSINESS IN THE SUGARCANE FARMING SYSTEM IN THE COMMUNITY LIVESTOCK CENTER AREA - Ferdi Fathurohman; Rita Purwasih (Journal of Social Research, 2022)
Abstract (English) Background: The development of beef cattle in quantity has had a very real impact on increasing people's income in improving their welfare. The development of animal husbandry, especially in beef cattle, has been carried out for generations and shows quite good development, including in the k groups. Objective: The purpose of this study is to identify a canvas business model consisting of nine elements and map out how strategies are used for the improvement and development of beef cattle agribusiness in the sugarcane farming system. Methods: The methods used are qualitative and quantitative methods with sequential exploratory design. Data collection was carried out with in-depth interviews and observations to farmers and institutions in 15 livestock groups around RNI's sugarcane plantations. The results obtained where the business model is good when viewed from nine elements according to the concept of business model canvas. Results: This study found that the strength of the livestock group was in the high category. Very high opportunities in the customer segment and high threats in value propositions. Conslusion: Therefore, livestock groups are advised to carry out business development in a way; adding to the customer segment, namely restaurants, DKM mosques and large companies, increasing the value proposition by opening meat stalls and opening meat processing businesses, creating websites, conducting consignments with several sales points and collaborating with universities and looking for freelance web developers. Keywords: Livestock Group, Canvas Business Model, Beef Cattle Agribusiness.